Implementation of an Eco-Efficiency Plan in the Construction of the Tunnel at the Chancay Megaport - Bernardo Toribio, Shirly Sofia (2024)
The implementation of an eco-efficiency strategy in the construction of the tunnel at the Chancay megaport was the main objective of the research presented. The sample consisted of 92 employees of the company. Additionally, the study was applied and used a non-experimental design. The study showed that between January and May 2022, there was a consumption of 79 234.402 kW of electricity, 6 360.76 gallons of fuel, 8.124 m³ of water, 19 000 kg of paper, 7 units of ink or toner, and an average of 3 209.2 kg of solid waste. After implementing an eco-efficiency plan that included training and other strategies to achieve the objectives, a significant reduction was observed: an average of 27.13% in electricity consumption, 7.16% in fuel, 23.14% in water, 21.05% in paper, 2.85% in ink and toner, and 3.21% in solid waste.